2021
DOI: 10.48550/arxiv.2105.12906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum Thermometry with a Dissipative Quantum Rabi System

Abstract: Dissipative quantum Rabi System, a finite-component system composed of a single two-level atom interacting with an optical cavity field mode, exhibits a quantum phase transition, which can be exploited to greatly enhance the estimation precision of unitary parameters (frequency and coupling strength). Here, using the quantum Langevin equation, standard mean field theory and adiabatic elimination, we investigate the quantum thermometry of a thermal bath surrounding the atom with quantum optical probes. With the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Such a term does not break the Z 2 parity symmetry of the Dicke model and the criticality survives this modification [829], but the critical coupling is now shifted. At the mean-field level, including photon losses with a rate κ and spontaneous emission of the atoms with a rate Γ, the new critical coupling becomes [895]…”
Section: The Dicke and Tavis-cummings Modelsmentioning
confidence: 99%
“…Such a term does not break the Z 2 parity symmetry of the Dicke model and the criticality survives this modification [829], but the critical coupling is now shifted. At the mean-field level, including photon losses with a rate κ and spontaneous emission of the atoms with a rate Γ, the new critical coupling becomes [895]…”
Section: The Dicke and Tavis-cummings Modelsmentioning
confidence: 99%
“…Furthermore, it has been shown [18] that finitecomponent phase transitions [19][20][21][22][23]-where the thermodynamic limit is replaced by a scaling of the system parameters [24][25][26][27][28]-can also be applied in sensing protocols. Surprisingly, quantum criticalities are versatile sensing resources that do not require the complexity of many-body system, as demonstrated by efficient dynamical protocols [29], the inclusion of quantum-control methods [30] or ancillary probes [31], the design of multiparameter estimation protocols [32] and of a critical quantum-thermometer [33], and by first experimental implementations [34].…”
mentioning
confidence: 99%

Critical parametric quantum sensing

Di Candia,
Minganti,
Petrovnin
et al. 2021
Preprint
“…It has also been shown [15,16] that, in spite of the critical slowing down, the framework of critical quantum metrology makes it possible to achieve the Heisenberg scaling, where the QFI grows quadratically in time and number of probes. Recent works [16][17][18][19][20][21][22][23][24] have shown that the framework of critical quantum metrology can be applied to a broad class of quantum optical models. Current solid-state and atomic technology allow for the implementation of these models in a controllable way, where their parameters can be tuned in real time.…”
mentioning
confidence: 99%